2018
DOI: 10.1371/journal.pcbi.1005972
|View full text |Cite
|
Sign up to set email alerts
|

Membrane perturbing properties of toxin mycolactone from Mycobacterium ulcerans

Abstract: Mycolactone is the exotoxin produced by Mycobacterium ulcerans and is the virulence factor behind the neglected tropical disease Buruli ulcer. The toxin has a broad spectrum of biological effects within the host organism, stemming from its interaction with at least two molecular targets and the inhibition of protein uptake into the endoplasmic reticulum. Although it has been shown that the toxin can passively permeate into host cells, it is clearly lipophilic. Association with lipid carriers would have substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
57
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 67 publications
(91 reference statements)
10
57
3
Order By: Relevance
“…and selected trajectories (traj./REMD). Root-mean square errors are within brackets.Exogenous addition of Aβ peptide to the bilayer 323In the REMD Aβ/DMPC and Cu-Aβ/DMPC simulations the DMPC bilayer is in the 324 liquid crystal phase at all the probed temperatures, consistently with similar MD 325 simulations reported in the literature[76]. The temperature dependence of the area per 326 lipid in Aβ/DMPC REMD simulation is displayed inFig 4,together with the available 327 experimental results for DMPC[75], the result for CMD at T =311 K for DMPC, and 328 the average of 10 CMD trajectories at T = 303 K described below.…”
supporting
confidence: 74%
“…and selected trajectories (traj./REMD). Root-mean square errors are within brackets.Exogenous addition of Aβ peptide to the bilayer 323In the REMD Aβ/DMPC and Cu-Aβ/DMPC simulations the DMPC bilayer is in the 324 liquid crystal phase at all the probed temperatures, consistently with similar MD 325 simulations reported in the literature[76]. The temperature dependence of the area per 326 lipid in Aβ/DMPC REMD simulation is displayed inFig 4,together with the available 327 experimental results for DMPC[75], the result for CMD at T =311 K for DMPC, and 328 the average of 10 CMD trajectories at T = 303 K described below.…”
supporting
confidence: 74%
“…Both AT2R and WASP are membrane associated proteins that have been suggested to be regulated by ordered microdomains that localize and facilitate assembly of signaling complexes (14)(15)(16). Our previous computational work suggested that toxin decreases line tension, thereby disrupting domain formation (17). Recent experimental work confirmed this prediction.…”
Section: Introductionmentioning
confidence: 84%
“…The thickness of the simulation box (z direction) is about 10 nm. In order to compare our research with the previous work of Lopez et al (17), we adopted the same MD simulation parameters for mycolactone, which were developed with the General Amber Force Field (GAFF) (22,23) and restrained electrostatic potential (RESP) charges. To verify the legitimacy of these parameters, we compared them to those generated with the General Automated Atomic Model Parameterization protocol (24) and found them to be reasonably consistent.…”
Section: All-atom Molecular Dynamics Simulationmentioning
confidence: 99%
See 2 more Smart Citations